Prediction of financial distress for multinational corporations: Panel estimations across countries. Issue 39 (21st August 2019) - Apergis, Nicholas; Bhattacharya, Mita; Inekwe, John
ABSTRACT: This research predicts ex-ante financial distress and analyses the link between financial distress, performance, employment, `and research and development (R&D) investment in the case of multinational companies (MNCs). The conditional logit and hazard models are employed to predict financial distress, while a conditional mixed process model is employed to obtain consistent and efficient estimates. Financial distress generates contractions in performance, employment, and R&D investment. Hedging against risk mitigates the effect of financial distress on R&D. Our findings vary across countries, for example, we find MNCs in Canada, Israel and the U.S. benefit from hedging against risk. The findings also indicate that ex-ante financial distress is detrimental to employment for Canada, the U.K., the Netherlands and the U.S. The findings indicate the MNCs play different roles across countries in contributing jobs, investment in R&D during the distress period.